2019
DOI: 10.1002/mmce.21932
|View full text |Cite
|
Sign up to set email alerts
|

A modified fractal‐shaped slotted patch antenna with defected ground using metasurface for dual band applications

Abstract: A novel modified fractal‐shaped slotted patch antenna employing metasurface at bottom plane along with partial ground has been proposed in this work for dual band applications with significant gain. A 4 × 5 order metasurface has been formed in the ground plane by introducing a periodic combination of two L‐type patches with centered C‐type shaped patch. The top conductor and the ground plane are designed on a 1.6 mm thick FR4 dielectric with the dimension of 28 × 28 mm2. The antenna is designed in such a way t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 30 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…It is found that the highest efficiency of an antenna is 83%, and 81% for the range of 2.4‐2.66 and 3.31‐3.57 GHz, respectively. Larger bandwidth coverage of 270 and 360 MHz at 2.4‐ and 3.5‐GHz band, respectively, when compared to a narrow operating bandwidth of fewer than 200 MHz was reported in References , , , and The efficiency reported in this research work is 83% which is higher than the efficiency reported in References , , , , and . A total of 16 different beams are produced by the proposed antenna with reduced complexity; however, the research work reported in References and gives a maximum of eight beams with increased numbers of active elements and patches. The maximum gain achieved by this antenna is 10.7 and 9.8 dBi at 2.4‐ and 3.5‐GHz band, respectively; however, the maximum gain reported in References , , , , and are less than 9 dBi. The design of antennas integrating multiple features, such as high gain, multiband, wide bandwidth, directive radiation, multiple radiation patterns for omnicoverage, low cost, and less complex structure, is of increasing demand for vehicular communication. This antenna satisfies all these requirements by using low‐cost FR4 dielectric material as substrate for reducing manufacturing cost, the multiple radiation patterns are realized from simple multiport excitation technique, high gain is attained by etching dual SR slots at the ground plane with the addition of reflector and hence this antenna is useful for high throughput satellite as well as base station‐enabled data services. …”
Section: Measurement Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…It is found that the highest efficiency of an antenna is 83%, and 81% for the range of 2.4‐2.66 and 3.31‐3.57 GHz, respectively. Larger bandwidth coverage of 270 and 360 MHz at 2.4‐ and 3.5‐GHz band, respectively, when compared to a narrow operating bandwidth of fewer than 200 MHz was reported in References , , , and The efficiency reported in this research work is 83% which is higher than the efficiency reported in References , , , , and . A total of 16 different beams are produced by the proposed antenna with reduced complexity; however, the research work reported in References and gives a maximum of eight beams with increased numbers of active elements and patches. The maximum gain achieved by this antenna is 10.7 and 9.8 dBi at 2.4‐ and 3.5‐GHz band, respectively; however, the maximum gain reported in References , , , , and are less than 9 dBi. The design of antennas integrating multiple features, such as high gain, multiband, wide bandwidth, directive radiation, multiple radiation patterns for omnicoverage, low cost, and less complex structure, is of increasing demand for vehicular communication. This antenna satisfies all these requirements by using low‐cost FR4 dielectric material as substrate for reducing manufacturing cost, the multiple radiation patterns are realized from simple multiport excitation technique, high gain is attained by etching dual SR slots at the ground plane with the addition of reflector and hence this antenna is useful for high throughput satellite as well as base station‐enabled data services. …”
Section: Measurement Resultsmentioning
confidence: 68%
“…The antenna employs two capacitively coupled square loops and the work focuses only on directivity enhancement and offers only a low impedance bandwidth in both the operating bands. In References and a dual‐band antenna based on meta‐material is reported for pattern reconfiguration using P‐type,Intrinsic, N‐type (PIN) diodes. However, additional complex reconfiguration structures are used with more number of parasitic elements to realize pattern reconfiguration.…”
Section: Introductionmentioning
confidence: 99%
“…Metasurfaces offer unprecedented opportunities to control and manipulate the amplitude, phase and polarization of electromagnetic waves. Since, the sub wavelength unit cell of the metasurface can be engineered to achieve any desirable functionality; therefore, they have found potential use in many applications such as antenna gain enhancement [1], radar cross section reduction [2], flat lensing [3], beam splitting [4], real-time holograms [5], absorbers [6]- [8], metasurface antennas [9], [10], polarization conversion and chipless radio-frequency identification (RFID) tags [5], [11]- [13]. Owing to its key role in many applications, the polarization control of EM waves has always been of central interest to scientific and engineering community.…”
Section: Introductionmentioning
confidence: 99%
“…Mousavi et al [8] designed a low-cost 1K element phased array system for mobile DBS reception. The reason behind using a microstrip antenna [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] is its compactness, less weight, low cost for fabrication, relatively less complicated matching network, and easy interface with microwave devices. Moreover, conventional design of microstrip antennas for Ku band applications [16,18,24,25] suffers from low gain, since the size of the antenna becomes small, which corresponds to lower surface area, that further deteriorates the gain.…”
Section: Introductionmentioning
confidence: 99%